Developing Design Sense in First-Year Architecture Students: A Pedagogical Approach to Basic Design - Tapaswini Mohapatra Samant (International Journal of Architectural Design and Planning, 2026)
This study explores the pedagogical significance of Basic Design Studios in shaping the foundational competencies of first-year architecture students. Serving as the foundation of architectural education, these studios cultivate essential skills in spatial awareness, creative thinking, and problem-solving. The research underscores how structured studio exercises, material explorations, and conceptual modeling collectively nurture an understanding of the interrelationship between space, form, and function. By emphasizing experiential and hands-on learning, students are encouraged to engage directly with design processes that transform abstract ideas into meaningful architectural expressions. The study adopts a reflective and process-oriented approach, highlighting the iterative nature of design learning – where observation, experimentation, and critique form a continuous cycle of improvement. Through interdisciplinary engagement that integrates art, geometry, and environmental understanding, students begin to perceive architecture as both an artistic pursuit and a scientific discipline. The studio environment becomes a dynamic platform where feedback-driven pedagogy enhances analytical ability, aesthetic judgment, and technical precision. Furthermore, the study emphasizes that effective design education depends not merely on output but on cultivating design thinking – the ability to interpret, visualize, and communicate ideas spatially. The integration of sensory perception, cognitive reflection, and material manipulation contributes to a holistic comprehension of design fundamentals. By bridging theoretical concepts with tangible practice, Basic Design Studios encourage students to evolve from passive learners into active creators capable of critical and contextual design responses. Ultimately, the findings advocate for a balanced and inclusive curriculum that harmonizes creativity with rigor, exploration with structure, and intuition with logic. Such an approach ensures that architectural education remains rooted in human experience while preparing students for advanced levels of design inquiry.
Keywords: architectural pedagogy; basic design; creativity in architecture; experiential learning; iterative design; spatial awareness